2021
DOI: 10.1103/physreva.103.033107
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the time-dependent electron dynamics in dielectric materials induced by two-color femtosecond laser pulses: Applications to material modifications

Abstract: Controlling the electron dynamics during laser-matter interactions is a key factor to control the energy deposition and subsequent material modifications induced by femtosecond laser pulses. One way to achieve this goal is to use two-color femtosecond laser pulses. In this paper, the electron dynamics in dielectric materials induced by two-color femtosecond laser pulses is studied by solving dedicated optical Bloch equations. This model includes photo-and impact ionization, the laser heating of conduction elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Such a nonoverlapping pulsed regime appears to be more advantageous for laser energy coupling inside bulk transparent materials as, for overlapped pulses, the local absorption efficiency can decrease due to the free-electron plasma shielding effect [32]. However, for overlapped bi-color pulses, it is necessary to introduce mixed wavelength ionization rates [22,23] which are still unknown. The orders of multiphoton ionization of fused silica, α, are equal to 6 and 3, respectively, for 800 nm and 400 nm irradiation; m e is the electron mass; τ c and τ tr are the electron collision time and the electron trapping time (1.28 fs and 150 fs, respectively).…”
Section: Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a nonoverlapping pulsed regime appears to be more advantageous for laser energy coupling inside bulk transparent materials as, for overlapped pulses, the local absorption efficiency can decrease due to the free-electron plasma shielding effect [32]. However, for overlapped bi-color pulses, it is necessary to introduce mixed wavelength ionization rates [22,23] which are still unknown. The orders of multiphoton ionization of fused silica, α, are equal to 6 and 3, respectively, for 800 nm and 400 nm irradiation; m e is the electron mass; τ c and τ tr are the electron collision time and the electron trapping time (1.28 fs and 150 fs, respectively).…”
Section: Mathematical Modelmentioning
confidence: 99%
“…It was shown that the order in which the pulses couple with the material is essential in bi-color ablation, with higher material removal rates when a shorter-wavelength pulse arrives first at the surface. There have also been several theoretical attempts to calculate the bi-color laser excitation of bandgap materials using ab initio approaches such as the optical Bloch equation [22] and the time-dependent density functional theory (TDDFT) [23]. Such calculations enable in-depth insights into ultrafast processes at the nanoscale, pointing out the potential advantages of bi-color irradiation regimes due to enhanced light absorption as compared to the single wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…The laser writing devices at sub-nanosecond scale need high NA objectives, being the problem of the low production efficiency. This problem can be well solved using two-beam interference [19] or holographic beam splitting method [20].Using ultrafast pulses with a designated characteristic wavelength can generate functional structures in solid materials, including dielectrics [21], polymers [22] and even semiconductors [23]. This inscription opens up a method to construct 2D or 3D structures in transparent materials.…”
Section: Introductionmentioning
confidence: 99%